Genome-wide association, RNA-seq and iTRAQ analyses identify candidate genes controlling radicle length of wheat - Xu, Fengdan; Chen, Shulin; Zhou, Sumei; Yue, Chao; Yang, Xiwen; Zhang, Xiang; Zhan, Kehui; He, Dexian (Frontiers in Plant Science, 2022)
The radicle, present in the embryo of a seed, is the first root to emerge at germination and its rapid growth is essential for establishment and survival of the seedling. However, there are few studies on the mechanisms determining radicle and then radical length in wheat seedlings, despite its importance as a food crop throughout the world. In this study, 196 wheat accessions from the Huang huai Wheat Region were screened to measure radicle length under 4 hydroponic culture environments over three years. Different expression genes and proteins (DEGs/DEPs) between accessions with extremely long [Yunong 949 (WRL1), Zhongyu 9302 (WRL2)] and short roots [Yunong 201 (WRS1), Beijing 841 (WRS2)] were identified in 12 sets of root tissue samples by RNA-seq and iTRAQ. The results indicated that the elongation zone was significantly longer in root accessions with long roots compared to the short-rooted accessions. A genome-wide association study(GWAS) identified4 stable chromosomal regions associated with radicle length.These regions on chromosomes 1A, 4A, and 7A explained 7.17% to12.93% of the phenotypic variation. The omics studies identified 24genes changed at both the transcriptional and protein levels. These genes were mainly involved in carbon fixation in photosynthetic organisms, photosynthesis and phenylpropanoid biosynthesis pathways.TraesCS1A02G104100 and TraesCS2B02G519100,are involved in the biosynthesis of tricin-lignins in cell walls, and may control the extension of cell walls in the radicle elongation zone. A combination of GWAS and RNA-seq analyses revealed 19 genes with expression changes in the four accessions, among which, TraesCS1A02G422700(a cysteine-rich receptor-like protein kinase 6, CRK6) also showedup-regulation in the comparison group by RNA-seq, iTRAQ and qRT-PCR. BSMV-mediated gene silencing also showed that TaCRK6 improves root development in wheat. Our data suggest that TaCRK6 is a candidate gene regulating radicle length in wheat.